“HARRY POTTER” TURKUMIDAGI ASARLARDA NEOLOGIZM VA OKKAZIONALIZMLARNING QO‘LLANILISH TADQIQI (Scientific journal of the Fergana State University, 2024)
Every language has enormous potential for improvement and expansion. The greatest potential of language development is its vocabulary. Neologisms and occasional words are of great importance in filling the lexical macro area of all languages with new forms. In the article, the peculiarities of neologisms and occasional words in the translation process were studied on the example of a literary work indirectly translated from English to Uzbek. Harry Potter books by Joanne Kathleen Rowling were taken as a basis for linguistic analysis. A correctly selected equivalent during the translation process determines the quality of the translation. Because it is the task of the translator to deliver the content without losing its original essence. During the analysis of theoretical literature, it can be noted that until today, a lot of work has been done to form and deepen the general understanding in the study of neologisms and occasional words. However, a number of issues, such as the cases of their conversion from English to Uzbek, have not yet been adequately resolved. Therefore, this article pays special attention to how well new words can be translated. Method of description, linguistic observation and description during research; analysis of linguistic literature on the research topic; continuous sampling and contextual analysis methods were used.Key words: neologism, occasionalism, linguistic macrofield, lexical system, equivalence, translation methods.